Gamification-Based Mobile Learning Assisted Language Learning for self-Directed Speaking Skill Improvement - Handikaningtyas, Tristania; Kuswandi, Dedi; Wedi, Agus (Akademika, 2025)
English speaking skills become an important skill to master in the 21st century as a global communication tool that can affect one's professional development. There are various challenges faced by learners in the learning process, such as low vocabulary acquisition and learning motivation. Therefore, gamification-based Mobile Assisted Language Learning comes as an innovative solution that can improve English speaking skills through self-directed learning. This study uses qualitative research with literacy studies related to the effectiveness of gamification-based Mobile Assisted Language Learning (MALL) on Self-Directed Learning (SDL) in improving English speaking skills. Data were obtained through SRL such as connected paper, Google Scholar, Research Rabbit, and ResearchGate. The analysis shows that the integration of MALL and gamification elements can increase learner motivation and engagement, resulting in interactive, personalized and flexible English learning. In learning, the SDL method provides positive implications in the form of learner freedom to organize learning according to their preferences which support the development of speaking skills effectively. The effectiveness can be seen from the increased accuracy of learners' pronunciation of words obtained from the instant feedback that affects their motivation and confidence. In addition, there is an increase in cognitive ability through increasing pronunciation accuracy and fluency in speaking English. The learners can memorize the vocabulary, understanding the meaning and apply the words in the appropriate contexts as evidenced by a significant increase in scores. In implementation, there are some challenges such as the potential for technology dependency and the need for targeted guidance in SDL. The results of this study are expected to provide information for teachers and learning material developers to design effective and relevant English learning strategies.